2015
DOI: 10.1007/s00109-015-1353-4
|View full text |Cite
|
Sign up to set email alerts
|

The biology and clinical implications of prostate cancer dormancy and metastasis

Abstract: Disseminated tumor cells (DTC) are detected early in the disease process in prostate cancer (PCa) patients and can persist after radical prostatectomy. DTC can remain dormant in patients with no evidence of disease for a prolonged period of time only to recur 10 or more years later. Recent advances in single cell genomics and transcriptomics have provided much needed insight into DTC biology and cancer dormancy in patients. With the development of new in vitro and preclinical models, researchers recapitulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…[24] For example, endothelial-derived trombospondin 1 (TSP1), bone morphogenic protein 7 (BMP7), transforming growth factor-β2 (TGF-β2) and growth arrest-specific 6 (GAS6) can mediate DTC quiescence in bone marrow. BMP7 is a TGF-β family member and is secreted by bone marrow stromal cells.…”
Section: The Hematopoietic Stem Cells Nichementioning
confidence: 99%
See 1 more Smart Citation
“…[24] For example, endothelial-derived trombospondin 1 (TSP1), bone morphogenic protein 7 (BMP7), transforming growth factor-β2 (TGF-β2) and growth arrest-specific 6 (GAS6) can mediate DTC quiescence in bone marrow. BMP7 is a TGF-β family member and is secreted by bone marrow stromal cells.…”
Section: The Hematopoietic Stem Cells Nichementioning
confidence: 99%
“…[34] CTC systems are being adapted to isolate and detect DTCs in the BM. [24] Another technique used for the detection of DTCs is the reverse transcriptase polymerase chain reaction (RT-PCR) to detect PSA. For this technique there is no enrichment required, due to high reaction sensitivity.…”
Section: Detection Of Circulating and Disseminated Tumor Cellsmentioning
confidence: 99%
“…Prostatic mesenchymal cells migrate from the primary tumor site and invade the bloodstream to metastasize to distant locations with the most frequent involvement being bone (90%), lung (46%), liver (25%), pleura (21%), and the adrenals (13%) 23. It is tacitly assumed that these mesenchymal cells then become dormant and after a prolonged period of dormancy, which can last for decades, an unknown trigger causes the reverse transition, MET 2425. MET enables tumor growth and leads to a clinically significant metastasis.…”
Section: Emt In Pcamentioning
confidence: 99%
“…While these models of dormancy are not mutually exclusive and might even coexist in the same patient, we will focus on cellular dormancy that is best supported by clinical evidence (Banys, Hartkopf, et al, 2012; Morrissey, Vessella, Lange, & Lam, 2015). Several studies showed that DTCs are frequently found in cancer patients with NED (Braun et al, 2005; Chery et al, 2014; Klein, 2009; Schardt et al, 2005), and the detection of DTCs in the bone marrow is associated with worse clinical outcome in many solid cancers (Braun et al, 2000; Hartkopf et al, 2014, 2015; Thorban, Rosenberg, Busch, & Roder, 2000; Wollenberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%